1979
DOI: 10.1080/00039896.1979.10667373
|View full text |Cite
|
Sign up to set email alerts
|

Collagen Breakdown and Ammonia Inhalation

Abstract: Measurement of several urinary metabolites of hydroxylysine indicates that considerable collagen degradation occurred in four individuals immediately after they had inhaled concentrated ammonia vapors. Since clinical and/or radiological evidence of intense upper respiratory and pulmonary inflammation were evident, it is likely that collagen degradation occurred at the level of the respiratory system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1980
1980
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Ammonia (NH 3 ) is an irritant substance and is used in petroleum refining and plastic production. The effect of ammonia on the respiratory mucosa has previously been studied [5][6][7][8], but not its effect on the olfactory neuroepithelium.…”
Section: Introductionmentioning
confidence: 99%
“…Ammonia (NH 3 ) is an irritant substance and is used in petroleum refining and plastic production. The effect of ammonia on the respiratory mucosa has previously been studied [5][6][7][8], but not its effect on the olfactory neuroepithelium.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of ammonia cardiotoxicity remains unclear, however recent study on antioxidant enzymes of the rat heart suggests that ammonia intoxication may induce oxidative stress (610). Cardiopulmonary arrest and tachycardia was reported in a six-month-old infant heavily exposed to ammonia fumes (615). These data indicate an adaptive response of the heart to oxidative stress under hyperammonemic conditions.…”
Section: Ammoniamentioning
confidence: 66%
“…One was in coma, another was lethargic and two had abnormal electroencephalographs showing encephalopathy (Hatton et al, 1979). They all survived.…”
mentioning
confidence: 91%
“…Only two studies of inhaled ammonia were found in a review of ammonia references (Ferguson et al, 1977;Hatton et al, 1979). One study included five men and one woman who worked in an Allied Chemical Company, Morristown, New Jersey.…”
mentioning
confidence: 99%